Ordinary differential equations in theory and practice - Mattheij, Robert M.M (John Wiley & Sons Ltd, 1997)
This monograph covers both analytical and numerical aspects of the study of ordinary differential equations, in combination with many practical models and examples chosen to illustrate the theoretical concepts. Emphasis is placed on initial value problems.